Observations of the Ultraviolet-bright Star III-60 in the Globular Cluster NGC 6723 - William V. Dixon (The Astrophysical Journal)
We have analyzed archival far-ultraviolet spectra of the UV-bright star III-60 in the globular cluster NGC 6723 obtained with the Far Ultraviolet Spectroscopic Explorer and the Cosmic Origins Spectrograph. We find that the star's photospheric parameters (effective temperature T _eff = 44,800 ± 1200 K, surface gravity $logg=4.89± 0.18$ , and helium abundance $logN({\rm{He}})/N({\rm{H}})=-0.84± 0.29$ ) are consistent with the values derived from its optical spectrum, suggesting that optically derived values are generally accurate for evolved stars with T _eff ≲ 50,000 K. Relative to the cluster's red giant branch stars, III-60 is enhanced in nitrogen and depleted in carbon and oxygen. The star exhibits strong P Cygni profiles in both components of the N v λ 1240 doublet, but the resonance lines of other species show no evidence of a stellar wind. The star's effective temperature and luminosity place it on the evolutionary tracks of stars evolving from the blue horizontal branch, but its high mass (∼1.2 M _⊙ ) indicates that it is the product of a stellar merger. Its helium, carbon, and nitrogen abundances suggest that it is following an evolutionary path similar to that of the low-carbon, intermediate helium-rich hot subdwarfs.